Low uptake of postnatal care services in northern Tanzania. (2nd January 2019) - Laisser, Rose Mjawa; Matovelo, Dismas; Kuzenza, Flora; Kidenya, Benson
Abstract : Background: High maternal and neonatal mortality is still a challenge in Tanzania. Postnatal care services are highly recommended to prevent these deaths; however, uptake of the services is unsatisfactory. Studies on health facility factors related to low use of postnatal care are also limited. Aims: To determine health facility factors that contribute to the low uptake of postnatal care services in 43 primary care facilities of Misungwi District, Tanzania. Methods: A validated checklist with secondary data from health facility records was used in data collection, which took place between April and June 2016. Findings: Findings showed that 40.6% of 2648 women who gave birth at the facilities returned for postnatal care. Inadequate numbers of midwives, medicines, beds and laboratory facilities were found. Conclusions: There is an urgent need to deploy midwives and improve non human resources for better maternal and infant outcomes.